The Investigation of polarization diversity in MIMO system at 2.4 GHz - Abd. Aziz, Mohamad Zoinol Abidin; A. Rahim, Mohamad Kamal; Abdul Kadir, Muhammad Faiz; Suaidi, Mohd Kadim; Daud, Zakiah; Jamaluddin, Mohd Hidayat (Penerbit Universiti Teknikal Malaysia Melaka, 2011)
concept of multiple input multiple output (MIMO) system using polarization diversity that can enhance the channel capacity and increase the data output performance of the system. The microstrip antenna array is designed, fabricated and measured at the desired operating frequency for this measurement. Computer Simulation Technology (CST) software is used to design and simulate the microstrip antenna array. The simulation and measurement data results are compared and discussed. The fabricated microstrip antenna is used to develop the Radio Frequency (RF) MIMO test bed system. The system measurement was conducted in Microwave Laboratory at Faculty of Electronic and Computer Engineering, University Technical Malaysia Melaka with the operating frequency of 2.4 GHz. The spatial diversity and polarization diversity are applied in measurement campaign to investigate the performance of the wireless MIMO channel. The data obtained from the measurement was post-processed using MATLAB software in order to calculate the MIMO channel capacity. The analysis focused on the effect of the MIMO channel capacity due to the proposed measurement setup configurations. The channel capacity was increased from 0.03 b/s/Hz to 0.09 b/s/Hz when polarization diversity is applied at both transmitter and receiver.